Perennial grass ecotype ecological and genetic response to local and non-local microbial inoculum is ecotype-specific - Hartung, Eli Siebach (Kansas State University, 2023)
Andropogon gerardii Vitman (big bluestem) is a dominant grass of the Great Plains that accounts for roughly 70% of the biomass of tallgrass prairies. Its broad distribution across a steep rainfall gradient in the Great Plains has given rise to locally adapted wet and dry ecotypes of this grassland species. Abiotic factors, such as rainfall, in the formation of ecotypes and local adaptation have been well-studied. However, much less is known about the role of biotic factors, such as soil microbiomes, in local adaptation. Soil microbiomes play a fundamental role in plant drought resistance and nutrient uptake. We used a reciprocal inoculation experiment in greenhouse to determine the role of local and non-local microbial communities on A. gerardii performance and local adaptation. We collected seed and rhizosphere soil samples from six A. gerardii populations, three from western Kansas (580 mm rainfall per year) representing the dry ecotype and three from southern Illinois (1167 mm rainfall per year) representing the wet ecotype. We isolated microbes from roots and native soil, cultured them in Reasoners 2A agar broth, and reciprocally inoculated wet and dry microbes (plus no-microbe control) weekly into common garden soil for 12 weeks under greenhouse conditions (6 replicates per treatment combination). Plant form and function were measured weekly for a variety of ecological responses. At the end of the experiment, leaf samples were collected for mRNA extraction to investigate differential gene expression. We found that ecotype determined most of our results. In addition to ecotype effects, inoculation increased total biomass, particularly of the dry ecotype by ~30% compared to control. Furthermore, ecotypes had higher chlorophyll absorbance when grown with local soil microbes, thus providing evidence of biotic local adaptation. Gene expression differed between the two ecotypes regardless of inoculum with over seven thousand genes differentially expressed between ecotypes. For the dry ecotype, selected upregulated genes involved those in photosynthesis, disease resistance, and zinc ion binding. Conversely, for the wet ecotype, notable selected genes were involved in response to auxin, detoxification, and defense. Inoculum was not a major driver of gene expression. However, of the few differentially expressed genes, plants grown with dry inoculum showed upregulation of genes relating to nitrate reductase and lipid binding, while plants grown with the wet inoculum showed upregulation of genes involved with abscisic acid biosynthesis, detoxification, and heat response. Furthermore, when ecotypes were inoculated with their local soil microbes, with whom they share an evolutionary history, we found major effects of inoculum origin on plant growth and development. In the dry ecotype, there was a strong positive correlation with increased chlorophyll absorbance and co-expression of differentially expressed genes related to electron capture, light response, and plant growth. For the wet ecotype, the co-expression of genes relating to biosynthesis, transcriptional regulation, and auxin signaling in the wet ecotype strongly correlated with its leaf area and biomass. Thus, our results showed diverse effects of inoculum origin on many unanticipated aspects of plant growth and development depending on ecotype. Our study highlights transcriptional pathways in A. gerardii ecotypes that are modulated by microbial communities thus impacting host form, function, and process. These results provide insight into how plants interact with native microbes and how researchers might harness microbiomes to increase plant productivity. As grasslands worldwide face climate pressures and anthropogenic impacts, the ability to harness beneficial microbial communities will be essential to preserve these ecosystems now and into the future. By matching plant hosts to specific beneficial microbes, we can potentially increase plant success and productivity.
Keywords: Andropogon gerardii; Gene expression; Local adaptation; Plant-microbe interactions; Rhizosphere